Pertunangan Anak di Bawah Umur Tinjauan dari Perspektif Hukum Keperdataan Indonesia - Nayla Utami Yasin; Nirwan Junus; Julius T. Mandjo (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The purpose of this study is to find out about the legalization of underage engagement from the perspective of civil law in Indonesia. The type of research used in compiling this study is normative legal research by taking an approach that includes community legal norms and forms of legal norms contained in laws and court decisions. Furthermore, by conducting a hierarchical analysis of the synchronization between one rule and another. The results of the study indicate that the legalization of underage engagement from the perspective of civil law in Indonesia where during the engagement period the two prospective brides and grooms are not yet allowed to have a relationship as a relationship between a husband and wife, the prospective bride and groom in principle still have the same relationship with the law of their relationship between people who are not mahram who are not yet bound by marriage. Therefore, all the prohibitions that apply to the relationship between men and women also apply to them, only the prospective bride during the engagement period may not be proposed to by someone else, because she is in the engagement of her prospective husband. That the legal consequences of underage engagement will have an impact on the cancellation of the engagement itself. Talking about cancellation, cancellation means fasakh or ending the validity of something that happened previously. In addition, it will affect gender.